Mongolia : Request for Stand-By Arrangement; Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2009)
This paper focuses on proposed Stand-By arrangement (SBA) for Mongolia. This proposed SBA would aim to smooth adjustment to the catastrophic terms-of-trade shock, restore health to the country's fiscal finances, and allow for exchange rate flexibility in line with market conditions. In addition, the IMF program would outline a clear macroeconomic framework to provide the basis for the authorities to approach the broader international community for financial support. Monetary policy will be calibrated to lower inflation while maintaining a flexible exchange rate and safeguarding international reserves.